If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5u=3+8u
We move all terms to the left:
5u-(3+8u)=0
We add all the numbers together, and all the variables
5u-(8u+3)=0
We get rid of parentheses
5u-8u-3=0
We add all the numbers together, and all the variables
-3u-3=0
We move all terms containing u to the left, all other terms to the right
-3u=3
u=3/-3
u=-1
| 4(3x-1)+5=61 | | 4(3n+5)=60 | | 1/2+x=8/15 | | 1+2(q-2)=4(q+2)-5 | | 7*b/4=-49 | | -5(n+8)=-10 | | 31=y/4+8 | | y+0,2(3-2y)=0,5(5y+2)-8 | | Y=15.5x+10 | | -12(4-x)=108 | | 16+y=37 | | 9.7t+3.4=9.5t | | 4x+20=7x+56 | | 3x+-18=20 | | n^2+7n=60 | | 9(-2x-5)=16 | | 1/3+2/3(q-2)=4/3(q=2)-5/3 | | 4x-x-x=18 | | -8(7x-3)=-88 | | -14.4c+3.92=-13.88-15.4c | | 4d+3=(2d-7) | | 40x=20x | | 3a–9+7=5a | | 4h=8+6h | | 10(6x-3)=90 | | 10x-2.6666666667-4x=6x | | 4x+20=21x+21 | | X-27=5x-3 | | 9x-20=10x+10 | | c/2=-12 | | 3(a–3)+7=5a | | 3g-(-19g)-12g+(-9g)-(-7g)=-8 |